Evaluation of a novel metal–organic framework as an adsorbent for the extraction of multiclass pesticides from coconut palm (Cocos nucifera L.): An analytical approach using matrix solid‐phase dispersion and liquid chromatography. Issue 16 (17th July 2017) - de Jesus, Jemmyson Romário; Wanderley, Kaline Amaral; Alves Júnior, Severino; Navickiene, Sandro
Abstract : We report the synthesis, characterization, and application of [Zn(1, 4‐benzenedicarboxylate)(H2 O)2 ] n, Zn(1, 4‐benzenedicarboxylate)0.99 (NH2 ‐1, 4‐benzenedicarboxylate)0.01 (H2 O)2 ] n, [Zn(1, 4‐benzenedicarboxylate)0.95 (NH2 ‐1, 4‐benzenedicarboxylate)0.05 (H2 O)2 ] n, and [Zn(1, 4‐benzenedicarboxylate)0.9 (NH2 ‐1, 4‐benzenedicarboxylate)0.1 (H2 O)2 ] n as sorbents for the extraction of multiclass pesticides from coconut palm. Liquid chromatography with ultraviolet diode array detection was used as the analysis technique, and the experiments were performed at one fortification level (0.1 μg/g). The recoveries were 47–67, 51–70, 58–72, and 64–76% for [Zn(1, 4‐benzenedicarboxylate)(H2 O)2 ] n, Zn(1, 4‐benzenedicarboxylate)0.99 (NH2 ‐1, 4‐benzenedicarboxylate)0.01 (H2 O)2 ] n, [Zn(1, 4‐benzenedicarboxylate)0.95 (NH2 ‐1, 4‐benzenedicarboxylate)0.05 (H2 O)2 ] n, and [Zn(1, 4‐benzenelate)0.95 (NH2 ‐1, 4‐benzenedicarboxylate)0.05 (H2 O)2 ] n, and [Zn(1, 4‐benzenedicarboxylate)0.9 (NH2 ‐1, 4‐benzenedicarboxylate)0.1 (H2 O)2 ] n, respectively, with relative standard deviation ranging from 1 to 7% ( n = 3). Detection and quantification limits were 0.01–0.05 and 0.05–0.2 μg/g, respectively, for the different pesticides studied. The method developed was linear over the range tested (0.01–10.0 μg/g) with r 2  > 0.9991. A direct comparison of [Zn(1, 4‐benzenedicarboxylate)0.9 (NH2 ‐1, 4‐benzenedicarboxylate)0.1 (H2 O)2 ] n with the commercially available neutral alumina showed that [Zn(1, 4‐benzenedicarboxylate)0.9 (NH2 ‐1, 4‐benzenedicarboxylate)0.1 (H2 O)2 ] n was a similar extracting phase for the pesticides investigated.